A Just Transition for Labour: The Challenges of Moves to a Circular Economy - Fairbrother, Peter; Banks, Marcus (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2023)
SummaryProposals for a just transition for labour have been largely restricted to debates about transitions from the coal and oil industries. However, the transitions under way, especially in the context of the climate crisis, are more widespread. Hence the debates about a just transition from carbon-intensive industries should be refined and extended; otherwise, there is a prospect of rhetorical gesturing and little substantive change. Alongside these debates, planning guidelines are in place to encourage the adoption of circular economy practices to address questions relating to material sustainability, especially in the context of the encroaching climate crisis. Relatively little attention has been given to the implications for work and employment relationships of realizing the increasingly popular ambition to reuse, recycle and re-manufacture material inputs, waste and end-of-life products. To address these themes, the focus here is on the importance of a developed worker-focused just transition in Australian housing construction, and by implication other industries. The argument is twofold. First, an effective worker-based approach means participative and engaged labour unions pursuing transition objectives. Second, moves toward a circular economy require a just transition for the workforce. Such a transition must be planned and inclusive, with workers and their organizations as active subjects in the process. Hence, different strategies are required when unions are not in a position to speak for the whole workforce. We propose that alliances based on unions and other bodies that support workers and their households (such as environmental and other advocacy groups) become critical to the creation of a sustainable and just circular economy. Alliance politics, supported by appropriate government regulation, can become the basis to overcome the partiality and fragmentation of union representation.AbstractProposals for a just transition for labour have been largely restricted to debates about transitions in coal regions. Yet a just transition for labour should apply to all industries. Alongside these debates, planning guidelines are in place to encourage the adoption of circular economy practices to address questions relating to material sustainability, especially in the context of the encroaching climate crisis. Surprisingly, few people have considered the implications of such changes for work and employment relationships. Unless a just transition is pursued, current inequalities in the housing construction industry are likely to intensify and remain embedded. The argument is that moves toward a circular economy in Australian housing construction require a just transition for the workforce. Such a transition must be planned and inclusive.